Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Solving equations by factoring . How would you solve this?
2x²-x-3


Sagot :

2x²-x-3=0 Factor this equation: 
(2x-3)(x+1)=0   Then let each factor equal to 0 to solve for x
    2x-3=0                     and                   x+1=0
     2x=3                                                x= -1
      x= 3/2    
                The equation is solved by factoring